Алелопатичні властивості Elytrigia repens (L.) Nevski - Didyk, N.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
Products of decay of shoots, roots of Elytrigia repens and their mixture have been studied in the model greenhouse experiment for their effect on soil allelopathic activity and biochemical properties in dynamics. High autotoxic activity has been established for the root decay products and considerably less one – for the shoots. It has been shown that phenolic acids and other phenol compounds were important carriers of autotoxicity.